On the Teachability of Moral - Yajun, Fang (Advances in Social Sciences Research Journal, 2021)
From the perspective of moral connotation and moral conditions, moral is essentially a tendency of human nature to be good, which embodies the practical wisdom of human beings. The article combines predecessors' discussion and research on moral education, and demonstrates that moral is teachable from two aspects: whether moral is innate and whether moral can be developed. Then three paths of moral education are proposed: the telling of moral stories; the development of moral education teaching materials; the awakening of cultural sympathy,in order to promote people’s moral understanding and moral practice.